The sources of information of the genealogical tourist: the influence of social networks and genealogical associations - Urrestarazu Capellán, Ricardo; Correa-Fernández, José; Sanchez-Cubo, Francisco (Elsevier, 2022)
The increased demand for genealogical travel to places of family origin in recent years and its consequent economic and social repercussions have justified the aim of this research to obtain the sources of information used by genealogical tourists to prepare for their trip, and the influence that genealogical associations and groups operating on the Internet have on them. For this purpose, a survey was carried out among 223 genealogy enthusiasts who participate in or consult these groups and associations. Through a descriptive statistical analysis of the data obtained, using frequencies and percentages for qualitative variables and means with standard deviations for quantitative variables, this work confirms the outstanding influence that social networks and genealogical associations and groups have on general family history research information, and on specific questions of tourist interest that genealogists receive, and the lesser influence of travel agencies and traditional media. On the other hand, their results support the idea that the main reasons for these tourists to travel are to visit places where their ancestors lived and to research their family history in public archives. All these issues have implications for public cultural and tourism administrations and private sector companies in promoting the provision of historical documentary resources and materials on the internet, as well as the activity of genealogical associations and groups.
Keywords: Genealogía; Turismo; Redes sociales; Genealogical tourism; Tourist promotion; Sources of tourist information; Social networks; Associations